2019
DOI: 10.1097/wad.0000000000000285
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Model of Factors Associated With Capability to “Live Well” for Family Caregivers of People Living With Mild-to-Moderate Dementia

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 47 publications
3
33
0
Order By: Relevance
“…Prior findings suggest that loneliness may have an influence on caregiver well-being. We identified loneliness as one of the psychological factors significantly linked with 'living well' in a comprehensive model examining the ability of caregivers of people with dementia to live well (a composite measure of life satisfaction, quality of life and well-being) (Clare et al, 2019). An earlier study of 49 caregivers indicated that caregivers of people with Alzheimer's disease reported greater loneliness and depression in comparison to non-caregivers and that loneliness was predictive of depression (Beeson, 2003).…”
Section: Background: Loneliness and Family Caregivingmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior findings suggest that loneliness may have an influence on caregiver well-being. We identified loneliness as one of the psychological factors significantly linked with 'living well' in a comprehensive model examining the ability of caregivers of people with dementia to live well (a composite measure of life satisfaction, quality of life and well-being) (Clare et al, 2019). An earlier study of 49 caregivers indicated that caregivers of people with Alzheimer's disease reported greater loneliness and depression in comparison to non-caregivers and that loneliness was predictive of depression (Beeson, 2003).…”
Section: Background: Loneliness and Family Caregivingmentioning
confidence: 99%
“…Loneliness has been linked to poor well-being as well as depression, anxiety and mental health problems (Cacioppo, Hawkley, & Thisted, 2010;Courtin & Knapp, 2017), and is a potential risk factor for the development of poorer physical health outcomes (Valtorta, Kanaan, Gilbody, Ronzi, & Hanratty, 2016) and mortality (Holt-Lunstad, Smith, Baker, Harris, & Stephenson, 2015). Although loneliness has been explored in a range of different populations, there are only a handful of studies focused on family caregivers (Chukwuorji, Amazue, & Ekeh, 2017;Ekwall, Sivberg, & Hallberg, 2005;Jones & Peters, 1992;McRae et al, 2009;Vasileiou et al, 2017) and few of these have examined loneliness in caregivers of people with dementia (Beeson, 2003;Beeson, Horton-Deutsch, Farran, & Neundorfer, 2000;Clare et al, 2019;Jaremka et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, a clear and sensitive discussion about the diagnosis, tailored to the stage of the condition and the priorities and needs of the person with dementia and those caring for them, should lead on to considering practical interventions to allow all involved to ‘live well with dementia’. 5 6…”
Section: Introductionmentioning
confidence: 99%
“…The symptoms of dementia can affect individuals' personal and social circumstances, creating challenges to living well [3]. Supporting people with dementia brings its own challenges, and unpaid carers may require support to maintain social roles and resources [4]. Individuals living with the condition may need to make demands on the time and resources of unpaid carers and on services provided by health and social care.…”
Section: Introductionmentioning
confidence: 99%